ABCG2 Polymorphism rs2231142 and hypothyroidism in metastatic renal cell carcinoma patients treated with sunitinib. Issue 3 (4th May 2019) - Werbrouck, Emilie; Bastin, Julie; Lambrechts, Diether; Verbiest, Annelies; Van Brussel, Thomas; Lerut, Evelyne; Machiels, Jean-Pascal; Verschaeve, Vincent; Richard, Vincent; Debruyne, Philip R.; Decallonne, Brigitte; Schöffski, Patrick; et al.
Abstract: Background and aim : Vascular endothelial growth factor receptor tyrosine kinase inhibitors (VEGFR-TKIs) cause significant adverse events including thyroid dysfunction, mainly hypothyroidism, in a considerable proportion of patients. In a series of metastatic renal cell carcinoma (mRCC) patients treated with sunitinib, we aimed to study the correlation between hypothyroidism and single nucleotide polymorphisms (SNPs) in genes involved in sunitinib pharmacokinetics and pharmacodynamics. Patients and methods : We included 79 mRCC patients who started sunitinib between November 2005 and March 2016. Serum thyroid function markers were collected at start and during sunitinib therapy. Germ-line DNA genotyping for 16 SNPs in 8 candidate genes was performed. Endpoints were time to increase in thyroid stimulating hormone (TSH) and time to decrease in T4 or free T4 (FT4) on day 1 and day 28 of each sunitinib cycle. Results : Patients with the ABCG2 rs2231142 CC-genotype had a significantly longer time-to-TSH-increase on day 1 (11 vs. 5 cycles; p  = 0.0011), and time-to-T4/FT4-decrease on day 1 (not reached vs. 10 cycles; p  = 0.013) and day 28 (28 vs. 7 cycles; p  = 0.03) compared to CA-carriers. Patients with the CYP3A5 rs776746 GG-genotype had a significantly longer time-to-TSH-increase at day 1 compared to GA-patients: 11 vs. 5 cycles ( p  = 0.0071). Significant associations were also found between PDGFRA rs35597368 and rs1800812 and time-to-TSH-increase at day 28. Conclusion : Polymorphism rs2231142 in the efflux pump ABCG2 is associated with hypothyroidism in mRCC patients treated with sunitinib.